For a phonic materialism - Milone, Gabriela (Universidad Nacional del Litoral, 2020)
The present work proposes the category of «phonic materialism», from the passage of the voice to the letter (Agamben). We will analyze the writing of the voice in argentian and latin american poetics: phonic games, sounds that coexist in different temporalities and spatialities, outside the rules of grammar and rhetoric. From the idea of Barthes of the «rustle of the language» (that utopia of a language where the phonic significant does not eliminate the «sense» but postulates it as a mirage) we will read in the writings of Juan Carlos Bustriazo Ortiz, Oscar del Barco, Andrés Ajens, Mauro Césari, the accentuation of the phonic level over the semantic one, from «phonic fictions». We will configure a cartography of phonic forces in the act of vocal exercises that write the matter of the voice.